The Evolutionary Characteristics of Lower Permian Keziliqiman Reefs in the Southwest Margin of Tarim Basin, Northwest China. (4th August 2022) - Wang, Yijun; Tang, Hongming; Yang, Guang; Wang, Zhenyu; Zhang, Yunfeng; Chen, Lei
Abstract : The Permian strata in the southwest Tarim Basin contain organic reefs with good exploration prospects. Based on observations of outcrops and thin section examination of the Permian Keziliqiman Formation reef in the Sangzhu section of Pishan County, Xinjiang, northwest China, the basic characteristics of the reef are studied. This organic reef, as a point reef which grew along the platform margin, has a complete subfacies system of base, core, front, back, and cap. The lithology of the lower zone of the core is mainly sponge bafflestone, while that of the upper zone is coral framestone. The development of reefs was controlled by the rise and fall of sea level. It was when the sea level rose in southwest Tarim Basin that the Keziliqiman reef gradually came into existence. Later, with rapid decline of sea level in that area, the Sangzhu section turned into a hot and dry supratidal zone, where algae began to flourish, dolomitization intensified, reef building organisms died en masse, and eventually the reef died. Paleontological and geochemical characteristics of the Sangzhu reef indicate that the sea-level decline in southwest Tarim Basin may be related to the Early Permian glaciers. Since then, the reef began to be transformed by diagenesis. But on the whole, its effect was not significant. Furthermore, its diagenetic process had more to do with marine fluids than with nonmarine fluids, for nonmarine fluids was powerful enough to affect bioclasts but powerless to affect micritic matrix.